A REVIEW OF ZAKAT INSTITUTION FINANCIAL PERFORMANCE: A DECADE STUDY FROM INDONESIA - Aminudin Ma'ruf; Aminah Hasyim; Anggrey Nurelsa Yandhi; Tilla Ira Sellani; Muhammad Iqbal Fatoni (Nurul Jadid University, 2024)
This study aims to measure the performance of zakat institutions by using activity ratios, efficiency ratios, zakat workers' fund ratios, liquidity ratios, and growth ratios from 2012 to 2021. This paper is qualitative research with financial ratios analysis. The sample of the study was taken from the independent auditor's report and annual reports of BAZNAS from 2012 to 2021. Financial statements are measured and reviewed using ratios to describe in-depth financial performance. The findings of this study provide the results of the calculation of the five ratios, showing good performance, efficiency and increasing quite significantly. Although some sub-ratios have yielded poor results, BAZNAS' performance has explained its business process activities are on track. The results of this study are expected to contribute to increasing the realization of zakat funds driving Indonesia's economic growth. This study humbly suggests BAZNAS for the need to improve the performance of human resources to be more optimal in collecting activities and controlling operational activities.